2019
DOI: 10.1002/pc.25349
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of surface modification of carbon fabrics and multiwall carbon nanotube incorporation for improving tribological properties of carbon fabrics/resin composites

Abstract: Surface modification of carbon fabrics (CFs) by nitric acid and multiwall carbon nanotube (MWCNT) incorporation into the resin matrix were simultaneously applied for CFs/resin composites to improve their tribological properties. The results show that surface roughness (Ra) of CFs increases from 8.20 to 15.10 nm after nitric acid treatment due to the remove of sizing agent on CFs surface. Surface hardness of the composites with 0.1 wt% MWCNT (CFR‐H‐0.1%T) is enhanced from 0.745 to 1.216 GPa compared with that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Wu [15] and Zhang [16] describe a strong dependence of the coefficient of friction on the resin type. Numerous publications report an increase in the wear resistance [17,18] and the coefficient of friction [18] of Carbon friction linings by introducing nanotubes into the resin material. The dynamic friction coefficient, friction stability, braking stability, thermal stability and wear resistance of the specimens with nanotubes are better than the specimens without nanotubes [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Wu [15] and Zhang [16] describe a strong dependence of the coefficient of friction on the resin type. Numerous publications report an increase in the wear resistance [17,18] and the coefficient of friction [18] of Carbon friction linings by introducing nanotubes into the resin material. The dynamic friction coefficient, friction stability, braking stability, thermal stability and wear resistance of the specimens with nanotubes are better than the specimens without nanotubes [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The combined form of magnetic and conductive particles additions could be better blocking elements in polymer matrix. [ 5 ] The magnetic particles may block the magnetic component and conductive particles may block the electric component of the incoming waves. The multiwall carbon nanotube MWCNT and Iron (III) oxide could be selected as reinforcing materials since they have excellent magnetic and conduction properties.…”
Section: Introductionmentioning
confidence: 99%
“…The multiwall carbon nanotube MWCNT and Iron (III) oxide could be selected as reinforcing materials since they have excellent magnetic and conduction properties. [ 5 ] Several authors concluded that the additions of compound particles of Cu‐Magnetite blend in to epoxy resin improved the microwave attenuation behavior of epoxy shield up to 38 dB. They have produced the compound form of particles by ball milling the particles up to 8 hours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the metal cases also need treatments of corrosion proof and baking enamel, which would increase the weight of the products. [26][27][28][29] Carbon fibers are prone to be hairy due to its poor shear strength during the weaving process and thus led to a failure product. Hence, in order to solve the hairy problem of carbon fibers, polypropylene is melt and coated on the surface layer of carbon/copper/polyester yarn by melting process, and form a double-layered structure.…”
Section: Introductionmentioning
confidence: 99%